Comparison of Haemodynamic Changes and Intubation Conditions during Awake Fiberoptic Oral Intubation using Conscious Sedation with Either Dexmedetomidine or Fentanyl: A Prospective Interventional Study - N Pallavi; Ahmedi Fathima; Rajeev Ratna Suresh Naik; V Swathi (Journal of Clinical and Diagnostic Research)
Introduction: Awake Fiberoptic Intubation (AFOI) is the preferred intubation technique in cases of anticipated difficult airway or unstable cervical spine injury. The patient will not be comfortable if it is performed without the appropriate sedative. AFOI achieves a better safety profile and a higher success rate due to preserved muscle tone and minimal risk of desaturation. Aim: To compare the effects of fentanyl and dexmedetomidine on haemodynamic changes and intubating conditions during AFOI in patients scheduled for elective cervical spine surgery. Materials and Methods: In this prospective interventional study conducted at Fortis Hospitals, Bengaluru, Karnataka, India, 84 patients aged 18 to 60 years with American Society of Anaesthesiologists (ASA) grade I or II, scheduled for elective cervical spine surgery requiring AFOI, were randomly assigned to two groups. Group A received dexmedetomidine at a dose of 1 μg/kg intravenously over 10 minutes, while Group B received fentanyl at a dose of 2 μg/kg intravenously over 10 minutes. Sedation levels were assessed using the Ramsay Sedation Score (RSS), and intubation was performed when the score reached 2 or higher. Intubation conditions were evaluated based on the cough score during bronchoscopy and the postintubation score. Statistical analysis, including appropriate tests such as t-tests or Chi-square tests, was conducted to assess differences in changes in pulse rate, Mean Arterial Pressure (MAP), and oxygen saturation during AFOI between the two groups and to evaluate the occurrence and significance of any adverse effects. Results: The mean age of the patients was 41.12±3.73 years in Group A and 40.21±3.03 years in Group B. Group A showed superior RSSs compared to Group B. Additionally, Group A demonstrated more favourable cough and postintubation scores in comparison to Group B. During the intubation and postintubation phases, Group B experienced a notable increase in pulse rate and MAP, whereas these haemodynamic parameters remained stable in Group A. Furthermore, Group A exhibited no significant desaturation events in contrast to Group B. Conclusion: Dexmedetomidine proved to be more effective than fentanyl for AFOI, providing superior intubating conditions by ensuring better patient comfort, which was assessed and confirmed through favourable scores on RSS (score of 2), cough score (score of 1), and postintubation score (score of 1). These advantages make dexmedetomidine the preferred choice for AFOI, offering a more favourable balance of sedation, haemodynamic stability and oxygenation.